2021
DOI: 10.1038/s41598-021-91526-3
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic modeling approach reveals promising therapeutic targets and antiviral drugs to combat COVID-19

Abstract: In this study we have developed a method based on Flux Balance Analysis to identify human metabolic enzymes which can be targeted for therapeutic intervention against COVID-19. A literature search was carried out in order to identify suitable inhibitors of these enzymes, which were confirmed by docking calculations. In total, 10 targets and 12 bioactive molecules have been predicted. Among the most promising molecules we identified Triacsin C, which inhibits ACSL3, and which has been shown to be very effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…Based on the results above, we suspected that targeting ACSL1 may help eliminate MHV-A59 infection. Two individual compound screening studies have found that Triacsin C inhibited SARS-CoV-2 replication [59,60], supporting our hypothesis. We first determined the effects of ACSL1 inhibitor Triacsin C on MHV-A59 infection in murine macrophages.…”
Section: Inhibiting Acsl1 Suppressed Mhv-a59 Infectionsupporting
confidence: 86%
“…Based on the results above, we suspected that targeting ACSL1 may help eliminate MHV-A59 infection. Two individual compound screening studies have found that Triacsin C inhibited SARS-CoV-2 replication [59,60], supporting our hypothesis. We first determined the effects of ACSL1 inhibitor Triacsin C on MHV-A59 infection in murine macrophages.…”
Section: Inhibiting Acsl1 Suppressed Mhv-a59 Infectionsupporting
confidence: 86%
“…On the other hand, S-palmitoylation is a unique protein lipidation process essential for viral invasion. Spalmitoylation of SARS-CoV-2 S protein has been reported to facilitate its anchor and fusion with the host cellular membrane receptor (Santos-Beneit et al, 2020). Thirdly, coronaviruses hijack the host cells for the formation of the replication and transcription complex, the double membrane vesicles (DMVs).…”
Section: Discussionmentioning
confidence: 99%
“…In this context the SARS-CoV-2 pandemic boosted research on metabolic antiviral host targets, which resulted in a multitude of potential candidates. While interference with many of these candidate targets already showed promising results in vitro and/or in vivo, there are even more potential targets that have been proposed, but not yet experimentally tested [ 121 ].…”
Section: Coronavirusesmentioning
confidence: 99%